Training for elite team-pursuit track cyclists - part I: a profile of general training characteristics - Stadnyk, A. M. J.; Stanley, J.; Decker, T.; Slattery, K. M. (International Journal of Sports Physiology and Performance, 2024)
Purpose To profile the training characteristics of an elite team pursuit cycling squad and assess variations in training intensity and load accumulation across the 36-week period prior to a world-record performance at the 2018 Commonwealth Games.